The relationship between M3 and consumer price index in the Czech Republic - Černohorská, Liběna; Klejzar, Vladimír (SciencePark Research, Organization and Counseling, 2017)
The aim of this paper is to analyze the influence of monetary aggregate M3 on consumer price index (CPI) in the Czech Republic. Cointegration this selected indicator M3 is demonstrated in relation to the development of CPI using the Engle - Granger cointegration test. These tests are applied to selected statistical data from the years 2003 to 2016. First step is to determine the optimum delay using Akaike criteria for all-time series analyzed. Then the presence of a unit root is analyzed using the Dickey - Fuller test. Based on the test results, time series are excluded which appear to be stationary. If the conditions are met, testing then continued with the Engle - Granger test to detect cointegration relations, which would determine a long-term relationship between selected variables. Based on these tests, it is found that at a significance level of 0.05, doesn´t exist cointegration relationship between M3 and CPI in the Czech Republic. Conclusions resulting from the verification of the hypotheses are supported with graphical visualization of data from which it is apparent that these hypotheses can be rejected.
Vztah mezi M3 a indexem spotřebitelských cen v České republice
Keywords: Akaike crieteria; Dickey – Fuller test; Engle – Granger cointegration test; CPI; M3; Akaike kritérium; Dickey-Fuller test; kointegrace; Engle - Granger tes; CPI; M3